Employee satisfaction, customer satisfaction, and financial performance: An empirical examination - Chi, C.; Gursoy, D (Pergamon, 2009)
The purpose of this study is to examine the relationship between employee satisfaction and customer satisfaction, and to examine the impact of both on a hospitality company's financial performance utilizing service-profit-chain framework as the theoretical base. Specifically, this study explores four major relationships: (1) the direct relationship between customer satisfaction and financial performance; (2) the direct relationship between employee satisfaction and financial performance; (3) the direct relationship between customer satisfaction and employee satisfaction; and (4) the indirect relationship between employee satisfaction and financial performance. Furthermore, this study examines the mediating role of customer satisfaction on the indirect relationship between employee satisfaction and financial performance. Data for this study was collected from employees, customers and managers of three- and four-star hotels. Structural equation modeling (SEM) with a two-step approach was utilized to empirically test the proposed hypotheses and the relationships between the constructs. Findings suggest that while customer satisfaction has positive significant impact on financial performance, employee satisfaction has no direct significant impact on financial performance. Instead, there is an indirect relationship between employee satisfaction and financial performance, which is mediated by customer satisfaction. © 2008.